Technique and Content in Faridoon Ali Amin's Stories - Sadoon, Asst.Prof.Dr.Saman E.; Rasul, Payman O. (Mitanni Journal of Humanitarian Sciences, 2023)
Abstract Kurdish literature existed in many genres of literature at the beginning of the twentieth century, with the emergence of the Kurdish journalism trend. Children's stories were one of the genres that emerged with newspapers, because newspapers and magazines reach every home where parents can read to their children. Faridun Ali Amin's position is important in children's stories, as he has once cared about children's stories, which were not as cultural in Kurdish. He has been trying to advise and guide children through children's stories. So, in the fifties, sixties and seventy centuries, this writer has set the story of children as a reason for education. In this way, he encouraged his parents to pay attention to this side. That's why he's published many children's story products of that time as books.